Prevalence of functional gastrointestinal disorders in infants and young children in China - Ying Huang; Serene Yaling Tan; Panam Parikh; Vanitha Buthmanaban; Shaman Rajindrajith; Marc Alexander Benninga (BMC, 2021)
Abstract Background The prevalence of functional gastrointestinal disorders (FGIDs) in children, particularly from Asia, is largely unknown. There are not many studies done in Asia especially using the Rome IV criteria. The aim of this study is to assess the prevalence of FGIDs in infants and young children in a representative sample in China. Methods A prospective, cross-sectional, community-based survey was conducted among healthy infants and young children between the ages of 0-4 years in Jinhua and Shanghai, China. A total of 2604 subjects (1300 subjects from Jinhua and 1304 subjects from Shanghai) completed a validated questionnaire on pediatric gastrointestinal symptoms. FGIDs in infants and young children were diagnosed using the Rome IV criteria. Results According to the Rome IV criteria, the prevalence of having a FGID in Chinese infants and young children is 27.3%. Infant regurgitation (33.9%) was the most common FGID among the 0-6 months old while functional constipation (7.0%) was the most common among the 1-4 years old. Risk factor analysis revealed that prevalence of infantile colic was higher with better maternal education and low birth weight. Prevalence of infantile regurgitation was significantly greater in males, living in a rural area, being exclusively breast fed at least up to 4 months and starting formula feeds within the first month. The risk of functional constipation was lower for infants who were delivered vaginally. Conclusions Infantile regurgitation was the most common FGID in Chinese infants while functional constipation was most prevalent among young Chinese children. Trial registration Netherlands Trial Registry Identifier: NL6973/NTR7161 .